The Effectiveness of Veyon Application Implementation in Client & Server Based Computer Labs - Muhammad Iskandarsyah; Rozali Toyib; Yulia Darnita; Agung Kharisma Hidayah (Jurnal Komputer, Informasi dan Teknologi, 2023)
Almost all government and non-government institutions already use computers and all media and work tools. But with a computer all these conveniences can also interfere with someone at work. For example, a student is following a practicum lesson but the student is instead busy with social media and games, so the learning process is not conveyed in the practicum activity.Monitoring computer activity carried out using the Client & Server method so that administrators will find it easier to monitor client computers connected to a computer network. In this application there is also a forced exit feature so that the client computer cannot carry out related processes outside of learning.After testing this application, it can be concluded that this application can monitor activities from client computers with a percentage of 80% so that network administrators can monitor processes and applications running on client computers. For testing the communication process between server computers and client computers using several computer network media, it was successful with a percentage of 80%.